PENGARUH PENGGUNAAN MEDIA CONGKLAK TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS V SD MUHAMMADIYAH JONGAYA - Nur Annisa; Baharullah; Sri Satriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using congklak media on students’ learning outcomes. The research employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest design. The sample of this study was also the population, consisting of 18 students, including 9 females and 9 males. Data were collected through observation and learning achievement tests. The obtained data were analyzed using descriptive and inferential statistics. The results showed that the mean pretest score of the students was 61.11 with a mastery percentage of 16.67%, which increased to 81.38 with a mastery percentage of 72.22% in the posttest. In addition, the hypothesis testing indicated a significant difference between learning outcomes before and after the use of congklak media. Based on these findings, it can be concluded that the use of congklak media has a significant positive effect on students’ mathematics learning outcomes, particularly on the topics of Least Common Multiple and Greatest Common Divisor.